Does Governing Law Affect Bond Spreads? - Ratha, Dilip; De, Supriyo; Kurlat, Sergio (World Bank, Washington, DC, 2016)
Controlling for bond and issuer characteristics, bond spreads are expected to be equal across different legal jurisdictions, and differences are expected to disappear through arbitrage. However, an analysis of 435 U.S. dollar–denominated bonds issued by 53 emerging market sovereigns during 1990-2015 reveals that after the financial crisis of 2008, the launch spread of sovereign bonds issued under U.K. law has been higher than those issued under U.S. law, by 130 basis points for BB+ bonds and 175 basis points for B- bonds. This effect was not significant for investment grade bonds. On average, bonds issued under U.K. law had weaker ratings and shorter tenors post-crisis. The post-crisis impact of governing law on sovereign bond spreads is not explained by collective action clauses, or first-time bond issuances. Instead, the difference seems to be related to the perception that U.S. law offers stronger investor protection, and that the investor base for bonds issued under U.S. law is larger than that for bonds issued under U.K. law. The difference in spreads persists in the secondary market even after 180 days, perhaps because of the lack of liquidity, as investors tend to buy and hold these more attractive bonds on a longer term basis.